Discursive rhythms and semantic-referential licenses: An approach to the sermonary of Fernando de Avendaño (1649) - Ezcurra Rivero, Álvaro (2012)
This paper provides an exemplary approach to certain persuasive and pedagogical strategies used in the Sermones de los misterios de nuestra santa fé católica . The sermons were published in Lima in 1649 by the creole priest Fernando de Avendaño. They were intended for the evangelization of the Andean region. I draw attention to two strategies, which I here call discursive rhythm changes and semantic-referential licenses. Both are analyzed linguistically and discursively.